Non‐invasive cell‐free fetal DNA testing for aneuploidy: multicenter study of 31 515 singleton pregnancies in southeastern China. (8th January 2020) - Xu, L.; Huang, H.; Lin, N.; Wang, Y.; He, D.; Zhang, M.; Chen, M.; Chen, L.; Lin, Y.
ABSTRACT: Objective: To analyze the non‐invasive prenatal testing (NIPT) for aneuploidy results of 31 515 singleton pregnancies in Fujian province, southeastern China, and assess its performance in low‐, moderate‐ and high‐risk pregnancies. Methods: Women were categorized into groups according to whether their risk for fetal abnormality was low, moderate or high. Cell‐free plasma DNA extracted from peripheral blood samples was subjected to low‐coverage whole‐genome sequencing. Standard Z ‐score analysis of the mapped sequencing reads was used to identify fetal aneuploidy, including the three main trisomies (T21, T18 and T13) and sex chromosome aneuploidy (SCA). NIPT‐positive results were confirmed by amniocentesis and karyotyping. The performance of NIPT for detection of T21, T18, T13 and SCA was assessed by calculating the sensitivity and specificity. Results: The rate of chromosomal abnormality detected by NIPT in the study population was 1.38%. A higher rate of chromosomal abnormality was found in the high‐risk group (1.57%) compared to the moderate‐risk (1.05%) and low‐risk (1.18%) groups ( P < 0.05). Sensitivity and specificity, respectively, were 98.96% (95/96) and 99.94% (31 274/31 292) for detection of T21, 100% (25/25) and 99.96% (31 352/31 363) for T18, 100% (7/7) and 99.97% (31 373/31 381) for T13 and 100% (61/61) and 99.74% (31 245/31 327) for SCA. Positive predictive values were high for T21 (84.07%) and T18 (69.44%) and moderate for T13 (46.67%) and SCA (42.66%). Conclusion: Our findings support the application of NIPT for reliable and accurate testing of the general population of reproductive‐age women for clinically significant fetal aneuploidy. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.